Application of the Intuitionistic Fuzzy Logic in Education - í‡itil, Mehmet (Communications in Mathematics and Applications, 2019)
In this paper, we have proposed an application of intuitionistic fuzzy set in high school determination using distance measures. The purpose of this paper is to interpret the relationship between students’ official test and the pilot test by means of distance measures in intuitionistic fuzzy sets. Distance measures have been compared and the most appropriate distance measure for this paper has been determined. This application of intuitionistic fuzzy set is very useful, because by calculating distance between each student and each school, the most proper school for each student has been determined. Available evaluation system could be renewed by using this application of intuitionistic fuzzy logic. Using this application in evaluation and determination system will have very beneficial results. The contribution of this new system are more stress-free, less anxious for testing, easier to implement, more economical and more advantageous in many ways. Thanks to this system, the enroll of students in high schools will not depend on a single test. Moreover, this is the first study to guide the students in the direction of students preferences in evaluation of success and this is the first one for evaluate with this application and offer recommendations in education.